Pollination implications of the diverse diet of tropical nectar-feeding bats roosting in an urban cave - Lim, Voon Ching; Ramli, Rosli; Bhassu, Subha; Wilson, John-James (PeerJ, 2018)
Background: Intense landscaping often alters the plant composition in urban areas. Knowing which plant species that pollinators are visiting in urban areas is necessary for understanding how landscaping impacts biodiversity and associated ecosystem services. The cave nectar bat, Eonycteris spelaea, is an important pollinator for many plants and is often recorded in human-dominated habitats. Previous studies of the diet of E. spelaea relied on morphological identification of pollen grains found in faeces and on the body of bats and by necessity disregarded other forms of digested plant material present in the faeces (i.e., plant juice and remnants). The main objective of this study was to examine the diet of the nectarivorous bat, E. spelaea, roosting in an urban cave at Batu Caves, Peninsular Malaysia by identifying the plant material present in the faeces of bats using DNA metabarcoding. Methods: Faeces were collected under the roost of E. spelaea once a week from December 2015 to March 2016. Plant DNA was extracted from the faeces, Polymerase chain reaction (PCR) amplified at ITS2 and rbcL regions and mass sequenced. The resultant plant operational taxonomic units were searched against NCBI GenBank for identification. Results: A total of 55 species of plants were detected from faeces of E. spelaea including Artocarpus heterophyllus, Duabanga grandiflora and Musa spp. which are likely to be important food resources for the cave nectar bat. Discussion: Many native plant species that had not been reported in previous dietary studies of E. spelaea were detected in this study including Bauhinia strychnoidea and Urophyllum leucophlaeum, suggesting that E. spelaea remains a crucial pollinator for these plants even in highly disturbed habitats. The detection of many introduced plant species in the bat faeces indicates that E. spelaea are exploiting them, particularly Xanthostemon chrysanthus, as food resources in urban area. Commercial food crops were detected from all of the faecal samples, suggesting that E. spelaea feed predominantly on the crops particularly jackfruit and banana and play a significant role in pollination of economically important plants. Ferns and figs were also detected in the faeces of E. spelaea suggesting future research avenues to determine whether the 'specialised nectarivorous' E. spelaea feed opportunistically on other parts of plants.